Hierarchical Fe3C−Mo2C−Carbon Hybrid Electrocatalysts Promoted through a Strong Charge‐Transfer Effect. Issue 19 (24th August 2020) - Yu, Deshuang; Ye, Min; Han, Silin; Ma, Yanchen; Hu, Feng; Li, Linlin; Peng, Shengjie
Abstract: Highly efficient, stable, and low‐cost catalysts for electrochemical water splitting play a critical role in promoting energy efficiency in the renewable hydrogen power‐related industries. In this study, nonprecious metal carbides composed of Fe3 C and Mo2 C supported by carbon nanoplates are prepared and utilized as bifunctional electrocatalysts for overall water splitting. Spatially confined annealing of the polydopamine‐coated metal precursors affords a structure containing porous cubes isolated by carbon nanoplates encapsulated with Fe3 C and Mo2 C nanoparticles. The hybrid electrocatalyst with a hierarchical structure, large surface area, and abundant exposed active sites benefits from efficient mass transport and more importantly the strong charge‐transfer effect between the iron and molybdenum moieties. Under strong alkaline conditions, the optimized Fe3 C−Mo2 C hybrid (with a Fe/Mo ratio of 1 : 2) requires a low overpotential of 274 and 301 mV for the electrocatalytic oxygen evolution reaction at current densities of 10 and 100 mA cm −2, respectively, accompanied with decent hydrogen evolution activity, thereby demonstrating efficient bifunctional electrocatalytic activity towards overall water splitting. Abstract : Charging towards water splitting : Spatially confined annealing of polydopamine‐coated metal precursors affords a Fe3 C−Mo2 C hybrid electrocatalyst with a hierarchical structure, large surface area, and abundant exposed active sites. Owing to efficient mass transport and strong charge transfer between Fe3 C and Mo2 C, the electrocatalyst demonstrates efficient bifunctional activity in overall water splitting.